The Malleability of Memory A Conversation with Elizabeth Loftus. - Burton, Howard (Ideas Roadshow Conversations Ser., 2020)
This book is based on an in-depth filmed conversation between Howard Burton and Elizabeth Loftus, renowned expert on human memory and Distinguished Professor of Psychological Science; Criminology, Law, and Society; Cognitive Science and Law at UC Irvine. This extensive conversation covers her ground-breaking work on the misinformation effect, false memories and her battles with ""repressed memory"" advocates, how getting expert memory testimony introduced in legal proceedings and the effect of DNA evidence on convincing judges of the problematic nature of eyewitness testimony. This carefully-e.